The management concept of exploring education cost sources through the role of religious leaders - Kgs. M. Roihan Adnan; Rifdah Hasan Parinduri; Karnia Karnia; Riskang Aj Pahruzi (Jurnal Akuntabilitas Manajemen Pendidikan, 2023)
Funding for education in schools often becomes a problem in the world of education. Because of the rapid development of the times, educational needs continue to increase, especially in efforts to improve the quality of education in schools. The purpose of this study is to describe how to manage the extraction of sources of education costs through the role of religious leaders. The method used is a literature review (literature review), namely by reviewing journals or news articles related to research. The analysis model is done by reducing data, presenting data, and drawing conclusions/verifying data. The results show that the management concept of exploring sources of educational costs through the role of religious leaders, which focuses on the community charity movement program, has several stages, namely: 1) Planning, starting from coordination meetings, job desc distribution, compiling work programs, implementation, monitoring, and evaluation; 2) Organizing, the division of tasks includes media managers, financial managers, public relations (PR), as well as field coordinators; 3) Implementation, namely building relationships with religious leaders, Â religious leaders preach to places of worship or in community activities such as house celebrations, thanksgiving, and others, media managers remind once a month to give alms, financial managers record income money and carry out financial accountability; 4) Supervision, which is carried out directly by the school principal or a person assigned by the school principal; 5) Evaluation, which is carried out directly or indirectly.